1988
DOI: 10.1104/pp.86.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Acclimation to Anoxia Induced by Low (2-4 kPa Partial Pressure) Oxygen Pretreatment (Hypoxia) in Root Tips of Zea mays

Abstract: ABSTRACFYoung intact plants of maize (Zea mays L cv INRA 508) were exposed to 2 to 4 kilopascals partial pressure oxygen (hypoxic pretratment) for 18 hours before excision of the 5 millimeter root apex and treatment with sictly anaerobic conditions (anoxia). Hypoxic accUmation pve rise to lrer amounts of ATP, to larger ATP/ADP and adenylate energy charge ratios, and to higher rates of ethanol production when excised root tips were subsequently made anaerobic, compared with root tips trferred directly from aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
105
2
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 21 publications
7
105
2
1
Order By: Relevance
“…The flooding resistance of a wide range of monocot and dicotyledonous species, both herbaceous and woody, is often associated, in part, with the capacity to develop such aerenchymatous roots (8,9,16,17,19,23). Additionally, metabolic acclimation to low oxygen improves the tolerance of roots to anoxia (29). ' The gaseous plant hormone, ethylene, is associated with a wide variety of responses in higher plant cells (3).…”
mentioning
confidence: 99%
“…The flooding resistance of a wide range of monocot and dicotyledonous species, both herbaceous and woody, is often associated, in part, with the capacity to develop such aerenchymatous roots (8,9,16,17,19,23). Additionally, metabolic acclimation to low oxygen improves the tolerance of roots to anoxia (29). ' The gaseous plant hormone, ethylene, is associated with a wide variety of responses in higher plant cells (3).…”
mentioning
confidence: 99%
“…Some investigations could not verify any effect of NO 3 -and NR on the energy metabolism in oxygendeficient roots. 22,23 However, other investigations have shown that NO 3 -supply to anaerobic root tissues led to an improved and 0.13 ± 0.03 g, respectively. The changes in the root and shoot dry weights (DW) and in shoot/root ratio were investigated after a three week period of hypoxic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For maize root tips, hypoxia rather than anoxia induced elevated activity of ADH (Saglio et al, 1988;Johnson et al, 1989). In maize protoplasts Walker et al, 1987), there were severalfold increases in Adhl mRNA with hypoxia (O2 concentra-Plant Physiol.…”
mentioning
confidence: 99%
“…The sudden imposition of anoxia with inhibition of oxidative phosphorylation caused a rapid decline in energy metabolism, and death of the apical meristem occurred in 15 to 20 h (Roberts et al, 1984a(Roberts et al, , 1984bSaglio et al, 1988;Johnson et al, 1989). During that time, there was no incorporation of I4C-labeled amino acids or 35S-labeled Met into proteins (D.J.…”
mentioning
confidence: 99%
See 1 more Smart Citation